Multi-robot cooperation inspired by immune systems - Razali, Sazalinsyah; Meng, Qinggang; Yang, Shuang-Hua (Society for the Study of Artificial Intelligence and Simulation of Behaviour, 2009)
Therefore, this research proposes an immune system based algorithm to achieve cooperative behaviour in a team of robots. Using the algorithm inspired by immune network theory, the robots can have the capability for performing their mission in an unstable environment.